Calcium isotope fractionation by osteoblasts and osteoclasts, across endothelial and epithelial cell barriers, and with binding to proteins - Töpfer, Eva Teresa; Rott, Jeremy; Bartosova, Maria; Kolevica, Ana; Machuca-Gayet, Irma; Heuser, Alexander; Rabe, Michael; Shroff, Rukshana; Bacchetta, Justine; Zarogiannis, Sotirios G.; Eisenhauer, Anton; Schmitt, Claus P. (American journal of physiology. Regulatory, integrative and comparative physiology, 2021)
Timely and accurate diagnosis of osteoporosis is essential for adequate therapy. Calcium isotope ratio (δ Ca-44/42) determination has been suggested as a sensitive, noninvasive, and radiation-free biomarker for the diagnosis of osteoporosis, reflecting bone calcium balance. The quantitative diagnostic is based on the calculation of the δ Ca-44/42 difference between blood, urine, and bone. The underlying cellular processes, however, have not been studied systematically. We quantified calcium transport and δ Ca-44/42 fractionation during in vitro bone formation and resorption by osteoblasts and osteoclasts and across renal proximal tubular epithelial cells (HK-2), human vein umbilical endothelial cells (HUVECs), and enterocytes (Caco-2) in transwell systems and determined transepithelial electrical resistance characteristics. δ Ca-44/42 fractionation was furthermore quantified with calcium binding to albumin and collagen. Calcified matrix formed by osteoblasts was isotopically lighter than culture medium by −0.27 ± 0.03‰ within 5 days, while a consistent effect of activated osteoclasts on δ Ca-44/42 could not be demonstrated. A transient increase in δ Ca-44/42 in the apical compartment by 0.26‰ occured across HK-2 cells, while δ Ca-44/42 fractionation was small across the HUVEC barrier and absent with Caco-2 enterocytes, and with binding of calcium to albumin and collagen. In conclusion, δ Ca-44/42 fractionation follows similar universal principles as during inorganic mineral precipitation; osteoblast activity results in δ Ca-44/42 fractionation. δ Ca-44/42 fractionation also occurs across the proximal tubular cell barrier and needs to be considered for in vivo bone mineralization modeling. In contrast, the effect of calcium transport across endothelial and enterocyte barriers on blood δ Ca-44/42 should be low and is absent with physiochemical binding of calcium to proteins.